Features of choosing the tactics and method of treatment of external joint frequencies of long external bones in people living with HIV - N. G. Doronin; S. N. Khoroshkov; S. L. Maksimov (Журнал инфектологии)
Objective. Develop an algorithm for determining tactics and parameters of their treatment to improve treatment outcomes. Methodology. Material and research methods. A statistical analysis of the treatment results of 90 HIV-infected patients aged from 23 to 54 years with extra-articular fractures of long bones of the extremities was carried out. When determining the tactics and method of treatment, the peculiarities of the effect of HIV infection, antiretroviral drugs, and opportunistic diseases on the patient’s body were not taken into account. Results. Non-infectious complications are characteristic of HIV-infected patients: sides of the postoperative wound (seromas, hematomas, discrepancy of wound edges, delayed crushing), aseptic loosening and migration of fixatives, delayed consolidation of fractures. The presence of a statistically significant relationship between the objective factors characterizing the course of HIV infection: the stage of the disease, the number of CD lymphocytes, the ratio of CD4 / CD8 lymphocytes, viral load and the risk of postoperative complications was revealed.Conclusion. The application of the developed algorithm allows you to objectify the procedure and provide an individual approach in determining the tactics and method of treatment for HIV-infected patients with extraarticular fractures of long bones of the extremities